Peran Radio Belitung Timur [RBT 89,7 fm] sebagai radio net dalam penyebaran informasi virus corona pada program talkshow covid-19 - Andy Armia; Rita Herlina (Islamic Communication Journal, 2021)
Public communication in the process of social interaction during the Covid-19 pandemic must continue. The media need to spread Covid-19 information to the public. This study aims to determine the role of RBT radio as Radio Net in managing the Covid-19 talk show program and create public participation to participate in discussions during the on-air Covid-19 talk show program, increasing public awareness of the Covid-19 virus. This descriptive qualitative research collects data through interviews, observations, and documentation as well as literature study from the website. The results show that the role of RBT radio in conveying information on Covid-19 greatly helps the public understand how to prevent the virus. The strategy is to utilize Facebook social media with the Covid-19 live streaming program packaged in the Talkshow format. RBT radio opens an interactive dialogue path with listeners, but it is not yet optimal. In increasing public awareness, RBT radio as often as possible plays Community Service Advertisements, and every broadcast discusses the Covid-19 news in Belgium itself. The substance of this research is the role of RBT radio as a government public relations radio in conveying Covid-19 information with the Covid-19 Talkshow program using the internet.